Proposed ram pump assisted water impounding project - Covita, Jore Nardee G.; Gagelonia, Robert Jr. B.; Quijencio, Carlinton L.; Ramos, Michael James A.; Tayaban, Jenah L.; Medestomas, Rodel V. (2014)
This research study's main objective is to design a structurally and environmentally safe Ram Pump Assisted Water Impounding Project that will meet the water demand of the rice field (thrice a year cropping) and vegetation area which is located at Brgy. San Antonio, Bambang, Nueva Vizcaya.
The researchers gathered data from different government agencies. Area of the catchment basin was compound using Google Earth Plus. The researchers designed the structure based on the data gathered and following the standards for Water Impounding Project, it has a capacity of 275, 286 cu.m. with a pond area of 5.4 Ha, a design that met the water demand requirement of the crops for the entire year suitable for three cropping.
The rice field area is 49.66 Ha and 1Ha for vegetation. At its critical condition, three meters of water will be left in the pond; hence raising fishes in the pond would be possible for the entire year. If drought will be experienced, the maximum capacity can hold up to 50 days to supply irrigating water. The financial cost estimate of the project is Php. 17,773,397.59.
Keywords: Ram pump -- Bambang (Nueva Vizcaya); Water Impounding Project (Bambang, Nueva Vizcaya)